Keterampilan Kolaborasi Siswa Melalui Penerapan Asesmen Autentik Berbantuan Model Cooperative Integrated Reading and Composition Scientific Approach (CIRSA) Pada Konsep Klasifikasi Hewan: (Student Collaboration Skills Through the Implementation of Authentic Assessment Assisted by the Cooperative Integrated Reading and Composition Scientific Approach (CIRSA) Model on Animal Classification Concepts) - Syahrani, Mala Tesla; Nuranti, Gina; Susanti, Yeti; Juhanda, Aa (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
This research aims to determine students' collaboration skills by applying the Cooperative Integrated Reading and Composition Scientific Approach (CIRSA) model assisted by authentic assessment. The research method used in this research is pre-experimental. The sample for this research is students in class VII A of SMP in Sukabumi Regency for the 2023 academic year /2024. The instrument in this research is an authentic assessment rubric for collaboration skills which includes self-assessment and peer assessment, collaboration skills based on indicators, as well as student responses Sukabumi Regency for self-assessment results is in the very good category with an average score of 87.06%, while for peer assessment it is in the very good category with an average score of 89.00%. The results of collaboration skills based on indicators are in the good category the average score was 78.88%, and the results of the student response questionnaire had an average score of 88.89% in the very good category. Abstrak. Penelitian ini bertujuan untuk mengetahui keterampilan kolaborasi siswa dengan menerapkan model Cooperative Integrated Reading and Composition Scientific Approach (CIRSA berbantuan asesmen autentik. Metode penelitian yang digunakan dalam penelitian ini adalah pra eksperimen. Sampel penelitian ini adalah siswa kelas VII A SMP di Kabupaten Sukabumi tahun ajaran 2023/2024. Instrumen pada penelitian ini berupa rubrik asesmen autentik kemampuan kolaborasi yang meliputi self assessment dan peer assessment, keterampilan kolaborasi berdasarkan indikator, serta respon siswa. Hasil penelitian menunjukkan bahwa berdasarkan penilaian menggunakan self assessment dan peer assessment kemampuan kolaborasi siswa kelas VII A SMP di Kabupaten Sukabumi untuk hasil self assessment berada pada kategori sangat baik dengan nilai rata-rata 87,06%, sedangkan untuk peer assessment berada pada kategori sangat baik dengan nilai rata-rata 89,00%. Hasil keterampilan kolaborasi berdasarkan indikator berada pada kategori baik dengan nilai rata-rata 78,88%, serta hasil angket respon siswa nilai rata-rata 88.89% berada pada kategori sangat baik.